2022
DOI: 10.1107/s2053230x22008767
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Rho-associated coiled-coil kinase 2 inhibitor belumosudil bound to CK2α

Abstract: The small molecule belumosudil was initially identified as a selective inhibitor of Rho-associated coiled-coil kinase 2 (ROCK2) and has recently been approved for the treatment of graft-versus-host disease. However, recent studies have shown that many of the phenotypes displayed upon treatment with belumosudil were due to CK2α inhibition. CK2α is in itself a very promising therapeutic target for a range of conditions and has recently been put forward as a potential treatment for COVID-19. Belumosudil presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, direct inhibition of ROCK2 kinase activity would be a risky approach because of the diverse physiological roles of ROCK2 [ 42 , 43 ]. The recent approval of belumosudil, a highly selective, low-molecular-weight ROCK2 inhibitor against chronic graft-versus-host disease [ 44 ] also indicates the multiple functional roles of ROCK2, although a recent study [ 45 ] suggested that the therapeutic effectiveness of belumosudil was partially due to inhibition of the protein kinase CK2α. We believe that by avoiding side effects, pathway-specific inhibitors could provide a solution for the reduction in Aβ levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct inhibition of ROCK2 kinase activity would be a risky approach because of the diverse physiological roles of ROCK2 [ 42 , 43 ]. The recent approval of belumosudil, a highly selective, low-molecular-weight ROCK2 inhibitor against chronic graft-versus-host disease [ 44 ] also indicates the multiple functional roles of ROCK2, although a recent study [ 45 ] suggested that the therapeutic effectiveness of belumosudil was partially due to inhibition of the protein kinase CK2α. We believe that by avoiding side effects, pathway-specific inhibitors could provide a solution for the reduction in Aβ levels.…”
Section: Discussionmentioning
confidence: 99%